Research And Community Service Information System At LPPM Universitas MBP Medan With Unified Modeling Language (UML) - Fauzi Haris Sibolon; Sartana, Sartana; Pasaribu, Maranata; Bangkit Iyoel Siregar (SEAN Institute, 2024)
Universitas Mandiri Bina Prestasis (UMBP) which was established in 2022 as a merger of two institutions, namely AMIK MBP with the Vocational Education program D-III Informatics Engineering and D-III Informatics Management and STIKOM with the S1 Informatics Engineering and S1 Information Systems Study Programs and the addition of 3 new study programs, namely S1 Software Engineering, S1 Accounting and S1 Entrepreneurship. Along with that, UMBP was born and developed with a commitment that was stated in the Vision of Becoming a Superior and Independent University in the field of Information Technology and Business with an Entrepreneurial Spirit at the National level in 2036